Pengaruh Fanatisme Supporter, Kualitas Pelayanan, dan Perilaku Konsumtif terhadap Keputusan Pembelian Produk Official Merchandise Persib Bandung - Nugraha, Nugie; Jaya, Rama Chandra (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research examines the impact of fanaticism supporters, service quality, and consumer behavior on purchasing decisions for official merchandise products of Persib Bandung. The study was conducted due to a decline in sales over the past year at the Persib store. Many factors contribute to this decline, including the perceived poor service and lack of interest in Persib Bandung merchandise, resulting in relatively low consumer purchase rates. The population in this study is consumers making purchases at the Persib store, consisting of 6,500 Persib Bandung supporters, with a sample of 100 respondents selected using non-probability sampling and purposive sampling techniques. The analysis includes validity testing, reliability testing, classical assumption testing, multiple regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The descriptive test results show that fanatical support, service quality, and consumer behavior highly influence purchasing decisions for official merchandise. Partial testing indicates that fanatic supporters and service quality have a significant positive effect on purchasing decisions, while consumer behavior has a significant negative effect on purchasing decisions. Furthermore, simultaneous testing shows that all three variables have a significant positive impact, with a correlation of 0.957 and a contribution of 91.7%.